ANISOTROPI MAGNETIK BATUAN DIORIT DARI TRENGGALEK,JAWA TIMUR - (NIM 20298524), Sudarningsih
Abstract : Magnetic anisotropy for diorite from Trenggalek, East Java has been studied with two methods namely anisotropy of anhysteretic susceptibility (AAS) and anisotropy of magnetic susceptibility (AMS). This study was carried out to find out which method is more effective. The results showed that the diorites have high degree of anisotropy averaging 37,1% for AAS and 23,7% for AMS method. In both methods, the directions of the principal axes are scatterred. Time-wise, AMS method is more effective than AAS. The AAS method, however, is more sensitive to ferromagnetic minerals with small grain size, while AMS method is also sensitive to paramagnetic minerals as well as .ferromagnetic minerals with large grain size. Inspite of their advantages and disadvantages, both methods can support each caber.